2021
DOI: 10.1097/mcg.0000000000001538
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Minimal Change Lesions Using Linked Color Imaging in Patients With Nonerosive Reflux Esophagitis

Abstract: Background and Aims: High prevalence of minimal change lesion (MCL) in nonerosive reflux esophagitis (NERD) patients is commonly recognized by many endoscopists. However, it is difficult to detect MCL with conventional white-light imaging (WLI) endoscopy. Linked color imaging (LCI), a novel image-enhanced endoscopy technology with strong, unique color enhancement, is used for easy recognition of early gastric cancer and detection of Helicobacter pylori infection. The aim of the study was to compare the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Therefore, we referred to two previous reports investigating the usefulness of LCI for the endoscopic diagnosis of minimal change esophagitis, 28 ,46 in which the addition of LCI on WLI increased the detection rate by 15%–20% compared with WLI alone, increased the inter‐observer agreement from “moderate” to “almost perfect” 28 and “moderate” to “substantial”, 44 and increased the intra‐observer agreement from “fair/moderate” to “moderate/substantial” 28 and “moderate” to “substantial”. 44 Second, we did not objectively evaluate the color difference between WLI and LCI using the CIE Lab color space system. 45 Third, it was impossible to use the images of WLI and LCI taken under the same conditions because LCI is created by pre‐processing and post‐processing technology, although we prepared paired images with as many similar compositions as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we referred to two previous reports investigating the usefulness of LCI for the endoscopic diagnosis of minimal change esophagitis, 28 ,46 in which the addition of LCI on WLI increased the detection rate by 15%–20% compared with WLI alone, increased the inter‐observer agreement from “moderate” to “almost perfect” 28 and “moderate” to “substantial”, 44 and increased the intra‐observer agreement from “fair/moderate” to “moderate/substantial” 28 and “moderate” to “substantial”. 44 Second, we did not objectively evaluate the color difference between WLI and LCI using the CIE Lab color space system. 45 Third, it was impossible to use the images of WLI and LCI taken under the same conditions because LCI is created by pre‐processing and post‐processing technology, although we prepared paired images with as many similar compositions as possible.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample size was small, and appropriate sample size to detect statistical significance was not calculated because of the lack of referable reports investigating the efficacy of LCI for the diagnosis of EoE. Therefore, we referred to two previous reports investigating the usefulness of LCI for the endoscopic diagnosis of minimal change esophagitis, 28 ,46 in which the addition of LCI on WLI increased the detection rate by 15%–20% compared with WLI alone, increased the inter‐observer agreement from “moderate” to “almost perfect” 28 and “moderate” to “substantial”, 44 and increased the intra‐observer agreement from “fair/moderate” to “moderate/substantial” 28 and “moderate” to “substantial” 44 . Second, we did not objectively evaluate the color difference between WLI and LCI using the CIE Lab color space system 45 .…”
Section: Discussionmentioning
confidence: 99%
“…LCI is a newly-developed IEE created by short-wavelength narrow-band laser light combined with white laser light, enabling brighter light in a distant area, and enhancing color differences between red and white [ 71 ]. It has been increasingly reported that LCI can improve various esophageal diseases, such as minimal change esophagitis [ 72 , 73 ], erosive esophagitis [ 74 ], Barrett’s esophagus, and esophageal adenocarcinoma [ 75 , 76 , 77 ]. There is a brief report showing that LCI could effectively detect an area of active inflammation, which was observed as yellowish mucosa, compared with cyan or light purple mucosa without active inflammation [ 78 ] ( Figure 5 ).…”
Section: Diagnostic Agreement Of Endoscopic Findings and Diagnosismentioning
confidence: 99%
“…Minimal changes are more easily recognizable using LCI, as the white areas appear whiter and the red areas appeared redder. 12,13…”
Section: Esophagusmentioning
confidence: 99%
“…Minimal changes are more easily recognizable using LCI, as the white areas appear whiter and the red areas appeared redder. 12,13 Barrett's esophagus is a risk factor for esophageal adenocarcinoma. As the incidence of GERD has increased, the incidence of Barrett's esophagus and esophageal adenocarcinoma has also increased.…”
Section: Clinical Application Of Lci In Esophageal Diseasesmentioning
confidence: 99%